Population, light, and the size distribution of cities - Christian Düben; Melanie Krause (Journal of Regional Science, 2021)
We provide new insights on the city size distribution of countries around the world. Using more than 10,000 cities delineated via geospatial data and a globally consistent city identification scheme, we investigate distributional shapes in all countries. In terms of population, we find that Zipf's law holds for many, but not all, countries. Contrasting the distribution of population with the distribution of economic activity, measured by nighttime lights, across cities we shed light on the globally variant magnitude of agglomeration economies. Deviations from Zipf's law are to a large extent driven by an undue concentration in the largest cities. They benefit from agglomeration effects which seem to work through area rather than through density. Examining the cross-country heterogeneity in the city size distribution, our model selection approach suggests that historical factors play an important role, in line with the time of development hypothesis.
Keywords: 320; agglomeration economies; cities; geospatial data; nighttime lights; population; urban concentration; Zipf's law